Nathan Bassett ledger - Bassett, Nathan, 1715-1791.; Barlow, Lemuel, 1758-1813.
Ledger containing Bassett's accounts, 1753-1783; accounts of Lemuel Barlow, 1799-1811; and accounts of a third person, maintained in the hand of Seth Barlow, 1812-1828. Documents the work of a New England blacksmith and the wage and price levels of the period. Includes genealogical data on the Bassett and Barlow families, 1685-1838.
Blacksmith in Sandwich, Mass.
Collection material in English.
Keywords: Barlow, Seth; Bassett family; Barlow family; Blacksmithing -- Massachusetts -- Sandwich; Prices -- Massachusetts; Wages -- Massachusetts; Massachusetts -- Commerce; Massachusetts -- Genealogy; Massachusetts -- History -- Colonial period, ca. 1600-1775.; Massachusetts -- History -- 1775-1865.; New England -- History -- Colonial period, ca. 1600-1775.; New England -- History -- 1775-1865.; Sandwich (Mass.) -- History; Blacksmiths